THE RELATIONSHIP BETWEEN COFFEE CONSUMPTION AND GERD SYMPTOMS IN UINSU SCIENCE AND TECHNOLOGY STUDENTS - Seri Rosidah Hasibuan,; Khaira, Nuri; Pratiwi, Atikah; Panjaitan, Muhammad Faiz; Wahyudi, Wahyudi (HEARTY, 2025)
Gastroesophageal Reflux Disease (GERD) is a common gastrointestinal disorder that occurs in productive age, especially among university students. One lifestyle factor that is thought to contribute to the incidence of GERD is coffee consumption habits. This study aims to analyze the relationship between coffee consumption and the incidence of GERD in students of the Faculty of Science and Technology, State Islamic University of North Sumatra. This study used a case control design with a retrospective approach. The sample amounted to 82 people, consisting of 41 cases and 41 controls, selected using accidental sampling technique. Data were collected through GERD-Q questionnaire and food frequency questionnaire, then analyzed using chi-square test. The results showed that regular coffee consumption was significantly associated with the incidence of GERD (p = 0,001) with an OR of 6.86 (95% CI: 2,5-19,1). In contrast, frequency of consumption per day and type of coffee did not show a statistically significant association with the incidence of GERD (p > 0,05). This study concluded that regular coffee consumption is a significant risk factor for the incidence of GERD in university students. Health education regarding wise coffee consumption is needed to prevent gastrointestinal disorders in the student population.